Home equity lines of credit and the unemployment rate: Have unemployed consumers borrowed themselves into the next financial crisis? - Michel, Norbert; Lajaunie, John P.; Lawrence, Shari; Fanguy, Ronnie (Journal of Banking & Finance, 2014)
Some economists argue the recent recovery has been so meager because many consumers have lost their main source of income and maxed-out their home-equity borrowings. Further, banks that were able to make consumer loans did so with less security because home prices fell so dramatically. This paper argues that at least part of that recovery story is purely anecdotal and, in fact, incorrect. In spite of the precipitous decline in home prices, the original price increases were so large that many homeowners still have/had adequate equity in their homes to borrow. The paper presents evidence that the average quarterly increase in aggregate home equity line of credit (HELOC) lending after housing prices began their decline is, statistically, no different than the average quarterly increase in HELOC lending before housing prices began their downward trend. The evidence also suggests that increased HELOC lending during the recession is not correlated with higher unemployment.